2015
DOI: 10.4103/0971-5851.158844
|View full text |Cite
|
Sign up to set email alerts
|

Hormone receptor status (estrogen receptor, progesterone receptor), human epidermal growth factor-2 and p53 in South Indian breast cancer patients: A tertiary care center experience

Abstract: Breast cancer, in India, is the second commonest cancer in females. Receptor status with ER/PR/Her 2 is now routinely done in patients with invasive carcinoma. The tumour suppressor gene, p53, is also present in most breast cancers. Proteins produced by a mutated p53 gene, accumulate in the nucleus of tumour cells and are detected by immunohistochemistry (IHC). We have undertaken this study with the aim to evaluate the ER, PR, HER-2 and p53 expressions in invasive breast carcinomas by IHC and to compare the HE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
36
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 27 publications
18
36
4
Order By: Relevance
“…32,58 The connection of PR positive and a slower histological progress in breast cancer observed in this study might also be a result of a negative association between PR and Her-2 positive in breast cancers 56 caused by the loss of PR protein due to Her-2 overexpression through the PI3K/Akt signaling pathway. 59 Relationship of Her-2, PR, ER, Ki-67 and p53 in signaling transduction pathways In this study, it was found that Her-2 overexpression was negatively connected with PR and ER expression and positively connected with Ki-67 positive and p53 positive, which was consistent with previous reports 30,32,37,44,46,49,53,59,60 This suggests that there might be some relationship among Her-2 and these genes in signal transduction pathways. Through MAPK and PI3K signaling pathways, Her-2 prevents apoptosis and promotes cell proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…32,58 The connection of PR positive and a slower histological progress in breast cancer observed in this study might also be a result of a negative association between PR and Her-2 positive in breast cancers 56 caused by the loss of PR protein due to Her-2 overexpression through the PI3K/Akt signaling pathway. 59 Relationship of Her-2, PR, ER, Ki-67 and p53 in signaling transduction pathways In this study, it was found that Her-2 overexpression was negatively connected with PR and ER expression and positively connected with Ki-67 positive and p53 positive, which was consistent with previous reports 30,32,37,44,46,49,53,59,60 This suggests that there might be some relationship among Her-2 and these genes in signal transduction pathways. Through MAPK and PI3K signaling pathways, Her-2 prevents apoptosis and promotes cell proliferation.…”
Section: Discussionsupporting
confidence: 92%
“…Her-2/Neu status was positive in only 6 cases (12.5%). Study done by Onitilo AA et al 28 and Patnayak R et al 29 showed somewhat similar results. We included early (Stage I and II) and locally advanced (Stage III) breast cancers in this study.…”
Section: Discussionsupporting
confidence: 59%
“…18 Another study from one tertiary care centre in India revealed 22.7% triple negative cases. 19 And one large study by Sandhu et al by combining the data from seventeen studies from India involving 7,237 breast cancer patients found 31% incidence of TNBC. 20 This finding is also alarming because the targeted therapy to ER, PR, HER2 receptor are of no use in TNBC causing lower disease free survival and overall survival.…”
Section: Discussionmentioning
confidence: 99%